Promoting Ethical Judgment in an Organisational Context - Cohen, Stephen (Journal of business ethics, 2013)
The essay argues that individual ethical judgment is a necessary ingredient in an organisation’s ethical performance. Attempts to systematise judgment, removing it from individual responsibility are not successful, and sometimes can even be counterproductive. Focus on systems of accountability can actually detract from the production of ethical behaviour. A number of examples are provided. Although it is much more difficult to produce, individual responsible decision-making and individual judgment should be the features that an organisation focuses on in its interest to promote ethical performance. Accountability systems are important; but they have very limited application toward production of an ethically excellent environment. The essay argues that there has been too much attention paid to accountability systems within organisations, and much too little paid toward the development and cultivation of individual ethical decision making and responsible behaviour.